Discovering and exploring existing perceptions of densification: The case of Orange Grove and Soweto. - Mfusi, Nkosikhona (University of the Witwatersrand; Faculty of Engineering and the Built Environment, 2016)
As the years go by, as the countries and cities continue to urbanise, the population growth of the world increases, and there emerges a growing concern of how to better equip cities to accommodate the rapidly increasing population. The prevailing question then becomes how do we develop cities to be able to withstand and to house the increase in population? Some cities have dealt with this predicament through creating new cities, or though encouraging the sprawling of existing cities. The cities that have chosen to think of a more sustainable solution for development have opted for using densification as a means to curb urban sprawl and resource consumption and in the process create more compact cities. The issue with opting for increasing densities is the fears that are associated with densification such as fears of overcrowding, loss of privacy, but most important the presiding fear of the myths and the memories of past failed densification attempts. The association of density with slums; degrading tower blocks; overcrowded, crime ridden neighbourhoods instead of with cities Paris, Toronto, Barcelona, Vienna or Singapore which are all examples of cities that have successfully densified in order to ensure survival. This report seeks to explore the perceptions that residents of suburban Johannesburg have regarding densification in attempts to help with the city’s progression towards a compact city. It aims to create and explore possible historical, economic, social or psychological links that may explain why residents have formulated or adapted the perceptions that they have.
What are the existing perceptions attached to residential densification in suburban Johannesburg?
Planning Honours Report 2016, Wits University